Strong key-insulated secure and energy-aware certificateless authentication scheme for VANETs. (October 2021) - Yang, Minghao; Chen, Jinhao; Chen, Yanan; Ma, Rong; Kumar, Sachin
Abstract: The rise of vehicular ad-hoc networks (VANETs) brings promise for guaranteeing road safety and improving traffic efficiency. Nevertheless, the pity is that the problems, such as messages authentication and privacy-preserving, that come with it seriously threaten the security and stability of the VANETs. For addressing these problems, in this paper, a pairing-free certificateless signature work for VANETs that supports parallel key-insulated is constructed. On the one hand, the presented work is constructed utilizing the elliptic curve rather than the costly pairing operation. In this way, each vehicle can generate or verify authentication message in a low energy consumption manner. On the other hand, the mechanism of parallel key-insulated is introduced in our proposed work where two helpers alternately assist the users for the periodical key updates, which can not only resist the key exposure but also reduce the risk of the helper's secret key exposure. Considering possible key exposure in the high dynamic VANETs scenarios, our scheme is more stable and feasible for VANETs environments compared with the existing works. Finally, our work is proved to be strongly key-insulated secure under the discrete logarithm assumption in the random oracle model. Meanwhile, the detailed performance comparisons demonstrate that our work is energy efficient and practical for VANET.